Jenis-jenis Bakteri Rizosfer Kawasan Tanah Mangrove Avicennia di Kelurahan Terusan, Kecamatan Mempawah Hilir, Kalimantan Barat - Riza Linda,, Dwi Nur Islamiah, Rahmawati, (Jurnal Protobiont, 2017)
Rhizosphere bacteria is one of organism types ultilized mangrove forest as one of media for proliferation activity. The rizosphere bacteria has significant contribution on mangrove forest chemically, physically and biologically. The aim of this study is to investigate the types of rhizosphere bacteria at Avicennia mangrove forest region located in Terusan Village, Mempawah Hilir sub-district, West Kalimantan. To collect sample of study, purposive sampling is applied. Bacteria isolation is conducted by using Nutrient Agar (NA) and Pour Plate method. The findings indicate that five genus of rhizosphere bacteria are found at Avicennia mangrove forest region located in Terusan village, Mempawah Hilir sub-district, West Kalimantan, specifically Acinetobacter, Bacillus, Pseudomonas, Serratia and Vibrio.